Impact of HLA-B51 on Uveitis and Retinal Vasculitis: Data from the AIDA International Network Registries on Ocular Inflammatory Disorders - ALİBAZ ÖNER, FATMA (My University, 2024)
Purpose: The clinical relevance of human leukocyte antigen (HLA) subtypes such as HLA-B51 on Behçet’s disease (BD)-related uveitis and non-infectious uveitis (NIU) unrelated to BD remains largely unknown. Methods: Data were prospectively collected from the International AIDA Network Registry for BD and for NIU. We assessed differences between groups (NIU unrelated to BD and positive for HLA-B51, BD-related uveitis positive for HLA-B51 and BD-related uveitis negative for HLA-B51) in terms of long-term ocular complications, visual acuity (VA) measured by best corrected visual acuity (BCVA), anatomical pattern, occurrence of retinal vasculitis (RV) and macular edema over time. Results: Records of 213 patients (341 eyes) were analyzed. No differences in complications were observed (p = 0.465). With regard to VA, a significant difference was detected in median BCVA (p = 0.046), which was not maintained after Bonferroni correction (p = 0.060). RV was significantly more prevalent in NIU-affected patients who tested positive for HLA-B51, irrespective of the systemic diagnosis of BD (p = 0.025). No differences emerged in the occurrence of macular edema (p = 0.99). Conclusions: Patients with NIU testing positive for HLA-B51 exhibit an increased likelihood of RV throughout disease course, irrespective of a systemic diagnosis of BD. The rate of complications as well as VA are comparable between NIU cases unrelated to BD testing positive for HLA-B51 and uveitis associated with BD. Therefore, it is advisable to perform the HLA-B typing in patients with NIU or retinal vasculitis, even in the absence of typical BD features.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ALERJİ; GÖZ HASTALIKLARI; Clinical Medicine (MED); CLINICAL MEDICINE; ALLERGY; OPHTHALMOLOGY; İmmünoloji ve Alerji; Oftalmoloji; Immunology and Allergy; Ophthalmology; AIDA network uveitis registry; Behçet’s disease; HLA-B51; non-infectious uveitis; retinal vasculitis